Implementing psychological strategies to improve the performance of women's Sepaktakraw athletes from Central Java in high-intensity competitions - Hermawan, Henry; Tasyafa, Fadia; Shidiq, Abdul Aziz Purnomo; Ma’muri, Fina Nurunnisa; Hidayat, Rohman (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
High-intensity competition and a dense match schedule demand stable mental readiness, particularly among female athletes, who are more susceptible to competitive anxiety, social pressure and mental fatigue. If not treated systematically through the right psychological approach, this condition has the potential to reduce focus, emotional stability, and competitive performance. This study aims to evaluate the effectiveness of implementing psychological strategies to improve the performance of Central Java Sepak Takraw putri athletes competing in two major competitions within five days: the Porprov and the POMNAS XIX qualifying rounds in 2025. The study employed an action research approach. The study population comprised female Sepak Takraw athletes from Central Java, with the sample consisting of athletes directly involved in the Porprov and POMNAS XIX 2025 qualification rounds. The data collection instruments included participatory observation, informal interviews, field notes and activity documentation. Data analysis was conducted descriptively and qualitatively by examining changes in mental state, focus on competition and team dynamics during the implementation of actions. The results showed a decrease in emotional stress and an increased focus on competing, as well as strengthened task cohesion between athletes. The success of the intervention is also reflected in the athletes' acquisition of two gold and one bronze medal at the POMNAS XIX 2025 event. In conclusion, the implementation of psychological strategies has been shown to effectively improve the mental stability and performance of Central Java women's Sepaktakraw athletes in high-intensity competitions. Subsequent research suggested that psychological assistance programmes should form an integral part of coaching athletes.